Pyocyanin Isolated from Pseudomonas aeruginosa: Characterization, Biological Activity and Its Role in Cancer and Neurodegenerative Diseases - Merve Tunca Koyun; Seda Sirin; Sinem Aslan Erdem; Belma Aslim (Brazilian Archives of Biology and Technology, 2022)
Abstract This study aimed to find a pigment of bacterial origin with protective/preventive activity against neurological injury and carcinogenesis, which may be used as a natural food additive in food activity or an active drug ingredient of an anti-neural injury/anticancer agent in the pharmaceutical industry. Within this scope, the Pseudomonas aeruginosa MB713 strain was used to produce pyocyanin. Characterization of the pyocyanin was carried out using UV-VIS, FT-IR, and GC-MS analyses. In addition, its inhibitory action on AChE and antioxidant activities were determined. The cytotoxic activities of the pyocyanin as well as its antiproliferative activities were detected. It was determined that the maximum production of the pyocyanin (51 μg/mL). The pyocyanin did not cause a cell death rate above 50% in L929 cells. The pyocyanin was found to exert an inhibitory effect on the AChE. The pyocyanin was found effective on all antioxidant parameters tested. The IC50 values of the pyocyanin on SK-MEL-30 and HT-29 cells were calculated as 72 and 179 μM, respectively. And due to the pyocyanin’s antioxidant and inhibitory effects on AChE, antiproliferative effects, and protective effects against neurodegenerative injury, the use of the pyocyanin as an active drug ingredient or a preservative food additive may be predicted. This situation can be clarified by conducting advanced molecular studies.